2015
DOI: 10.2119/molmed.2015.00096
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of miR-181a on the Renal Transcriptome and Blood Pressure

Abstract: MicroRNA-181a binds to the 3' untranslated region of messenger RNA (mRNA) for renin, a rate-limiting enzyme of the renin-angiotensin system. Our objective was to determine whether this molecular interaction translates into a clinically meaningful effect on blood pressure and whether circulating miR-181a is a measurable proxy of blood pressure. In 200 human kidneys from the TRANScriptome of renaL humAn TissuE (TRANSLATE) study, renal miR-181a was the sole negative predictor of renin mRNA and a strong correlate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 57 publications
2
66
0
Order By: Relevance
“…Moreover, we have previously found that miR‐181a was differentially expressed in human and mouse hypertensive kidneys . Consistent with the present study, we have also shown recently that circulating miR‐181a was associated with higher systolic and diastolic BP, through regulation of renin and pathways associated with the immune system and inflammation, consistent with immune system activation in heart failure . The circulating miRNA miR‐30e‐5p is down‐regulated in patients with acute heart failure .…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, we have previously found that miR‐181a was differentially expressed in human and mouse hypertensive kidneys . Consistent with the present study, we have also shown recently that circulating miR‐181a was associated with higher systolic and diastolic BP, through regulation of renin and pathways associated with the immune system and inflammation, consistent with immune system activation in heart failure . The circulating miRNA miR‐30e‐5p is down‐regulated in patients with acute heart failure .…”
Section: Discussionsupporting
confidence: 91%
“…More recently, we demonstrated that in two independent cohorts, serum levels of miR-181a correlated with systolic blood pressure. [16] Interestingly however, this association was opposite to that expected -increased miR-181a levels were associated with elevated blood pressure. Furthermore, this association was independent of circulating renin levels, suggesting that the effects of miR-181a may be mediated by mechanisms other than renin inhibition.…”
Section: Circulating Micrornas and Existing Mechanisms Of Blood Pressmentioning
confidence: 89%
“…In an illustration of this, our group utilised circulating miR-181a to gain a deeper understanding of its association with blood pressure. [16] In 2011, Marques et al…”
Section: Circulating Micrornas and Existing Mechanisms Of Blood Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-1β, IL-6, and TNF-α) in blood tissues of humans with chronic inflammation, as well as blood of LPS-treated mice [46]. Additionally, miR-181 expression in human kidney tissues were found to be associated with increased transcription of genes of inflammation pathways [47]. As the biological relevance of miRNAs is linked to their prevalence [48], we considered examining changes in levels of miR-181 molecules in in vivo infection models for henipaviruses.…”
Section: Resultsmentioning
confidence: 99%